Ten new species of Cladonia (Cladoniaceae, Lichenized Fungi) from the Guianas and Venezuela, South America - Ahti, Teuvo; Sipman, Harrie J. M. (Phytotaxa, 2013)
The diversity of the lichen family Cladoniaceae in the Neotropics is apparently underestimated. A revision of the family for the Flora of the Guianas resulted in the description of 10 species new to science from Northern South America: Cladonia cayennensis; Cladonia flavocrispata; Cladonia isidiifera; Cladonia maasii; Cladonia mollis; Cladonia persphacelata; Cladonia recta; Cladonia rupununii; Cladonia subsphacelata; Cladonia termitarum.